THE EFFECT OF THE HYPERBARYC OXYGEN THERAPY ON THE QUALITY OF LIFE AND THE STATE OF MICROCIRCULATION IN PATIENTS WITH SYSTEMIC SCLEROSIS - Pocevski, Božidar P; Pavlov-Dolijanović, Slavica (Medicinski podmladak, 2019)
Introduction: Systemic sclerosis (SSC) is a rare, chronic, progressive, severe illness with unknown etiology and characteristics of impaired microcirculation. The effect of hyperbaric oxygen therapy (HBOT) is reflected in the efficiency of pure oxygen under pressure greater than atmospheric and it is main indication for the application in the state of disturbed microcirculation.Aim: The aim was to examine the effect of HBOT on the quality of life and the state of microcirculation in patients with SSc.Material and methods: The research represents retrospective study which involved 18 female patients with SSc. All patients completed the HAQ, SySQ and TIFS questionnaires and all basic laboratory analyzes, as well as total anti-nuclear antibodies (ANA), anti-centromer antibodies (ACA), and anti-topoisomerase-1 antibodies (Anti-Scl-70). Rodnan skin score, capillaroscopy, and diffusion spirometry were made and values of forced vital capacity (FVC) and lung diffusion capacity for carbon monoxide (DLco) were taken.Results: FVC values were 96.61 ± 13.44 (78 - 122) before departure, but after treatment they were 115.94 ± 16.69 (82 - 135). DLco values were 73.61 ± 6.63 before departure, after departure results were 87.33 ± 9.30. ANA antibodies were positive in 38.9%, ACA were positive in 22.2%, and Anti-Scl-70 were positive in 16.7%. The mean value of ESR was 20.5 (4 - 42) before going to the hyperbaric chamber, and after departure it was 12 (3 - 27).Conclusion: Our research has shown that HBOT has a significant effect on patients with SSc, but further research is needed to determine the exact effect of HBOT on this disease.